Perencanaan Strategis, Operasional, dan Manajemen Risiko pada Aplikasi Jasa Titip Barang “Titip.In” - Hulman Wesly; Tantri Yanuar Rahmat Syah; Dimas Angga Negoro; Suwarto, Suwarto (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The "Titip.in" goods delivery service application was developed as a solution to overcome the challenges in the delivery service industry in Indonesia which is still developing. Currently, the delivery service market in Indonesia is dominated by individuals who run informal businesses through social media such as Instagram, WhatsApp, and Facebook. From an operational perspective, Titip.in adopts the latest technology, including microservices architecture and integration with payment gateways, to ensure a scalable, secure, and efficient system. Operational processes are designed to minimize risks such as damage to goods, late delivery, and logistics complexity. Titip.in also implements integrated supply chain management to support smooth delivery processes. With an innovative approach, advanced technology support, and a well-planned business strategy, Titip.in is ready to become a pioneer in the transformation of the delivery service industry in Indonesia. The combination of superior features, transaction security, and a focus on user satisfaction ensure that Titip.in is able to present relevant and competitive solutions in the market. Supported by positive financial indicators and a solid risk mitigation strategy, this business has promising growth potential and strong competitiveness amidst industry challenges. With a commitment to continue to innovate, Titip.in is determined to realize its vision as the number one trusted titip service application in Indonesia, presenting safe, efficient, and high-quality services for all users.